Regenerative and Positive Impact Architecture Learning from Case Studies - Attia, Shady (SpringerBriefs in Energy,, 2018)
This book is a guide to energy efficiency and environmental impact assessment in high-performance buildings projects. It compares four state-of-the-art buildings to examine the steps needed for a transition from negative impact reduction architecture to positive impact regenerative architecture, utilizing life cycle analysis. The book provides a solid grounding in the areas of energy-efficient building and building materials life-cycle assessment, discussing carbon efficiency within a wider context that includes its technical, socio-cultural and environmental dimensions and covers the key areas for green buildings performance (operational and embodied energy). The analysis and comparison of four case studies of state-of-art modern building projects in Europe and North America serve as inspiring examples for architects and building professionals in the fields of high performance buildings, ecological materials and carbon efficiency.